The Importance of Breastmilk in Acute Neonatal Enterocolitis and Other Enteric Disease - Tri Ruspandji; Suharyono Suharyono; Aswitha Budiarso; W.A.F.J. Tumbelaka; E.M. Halimun (Paediatrica Indonesiana, 1979)
In the Department of Child Health, Dr. Cipto Mangunkusumo Hospital, a case of necrotizing enterocolitis with resection about 50 cm of the ileum was reported.